Al-Jahiz (D. 868/9) on the Virtues of ‘Ali ibn Abi Thalib (D. 661) and the Limit of Ijma’ - Annas Rolli Muchlisin (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The study of al-Jahiz among researchers and historians of the classical Islam has shed more light not only on the man and his intellectual engagement but also on the general Islamic intellectual history, especially in the ninth century Bagdad, the capital city of the ‘Abbasid kingdom. This article examines how al-Jahiz, as an enthusiast debater, dialectician, and polemicist, engaged himself in debates concerning the virtues of ‘Ali ibn Abi Thalib and his caliphate status. This is a literature study of al-Jahiz’s works, complemented by secondary relevant sources. This study reveals that in debating this particular issue which had been highly controversial by his time, al-Jahiz differed from both his fellow Mu‘tazila thinkers and hadith transmitters, and even argued against ijma’,the consensus argument, which was and is still regarded as undisputed argument by many Islamic law scholars. His intellectual bravery then allowed him to freely articulate his ideas and stand as an independent and original thinker.